2022
DOI: 10.3390/land11050616
|View full text |Cite
|
Sign up to set email alerts
|

A Geographic Analysis on Rural Reconstruction-Transformation-Revitalization: A Case Study of Jianghan Plain in China

Abstract: At the beginning of the 21st century, with the rapid advancement of industrialization and urbanization, production factors such as population, capital, and land between urban and rural areas in China have gradually shifted to non-agricultural fields, the structure and function of rural territorial systems have been reconstructed and transformed therewith. In response to the relatively declining villages, the Chinese government proposed rural revitalization strategy. Taking the human–land relationship as the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
7
0
1
Order By: Relevance
“…Based on the balance and coordination of multi-functional space in cultivated land, this paper reconstructs the zoning scheme primarily based on the difference in internal structural characteristics between different functions within the same area. The result of the zoning process is intended to maximize the dominant functional advantages of cultivated land in different regions and achieve the objective of “fostering strengths and avoiding weaknesses.” In light of the obvious regional differences in the multi-functionality of cultivated land, it is necessary to propose differentiated and diverse multi-function utilization and management policies in order to optimize the functional layout of cultivated land [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the balance and coordination of multi-functional space in cultivated land, this paper reconstructs the zoning scheme primarily based on the difference in internal structural characteristics between different functions within the same area. The result of the zoning process is intended to maximize the dominant functional advantages of cultivated land in different regions and achieve the objective of “fostering strengths and avoiding weaknesses.” In light of the obvious regional differences in the multi-functionality of cultivated land, it is necessary to propose differentiated and diverse multi-function utilization and management policies in order to optimize the functional layout of cultivated land [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies on the impact of population urbanization on human capital [74][75][76] and family capital [77,78] accumulation, but from the perspective of urbanization, it is found that the process of urbanization will affect various aspects of society [79][80][81]. In the process of population urbanization, the change in social population structure will improve the basic platform of the individual [10,62], and the individual human capital will be enhanced [75].…”
Section: Population Urbanization and Capital Compositionmentioning
confidence: 99%
“…The integrated factor system summarizes the overall characteristics of the system reconstruction and provides accurate information for the identification of dominant factors. Therefore, based on the previous results of our research group [55], RRC, RX, RY, and RZ were used to denote the comprehensive, economic, social, and spatial restructuring indexes of a certain rural area, respectively, with their numerical magnitudes reflecting the degree of drastic structural changes in the rural regional system. The measurement index system is shown in Table 1.…”
Section: Measurements Of Rural Restructuringmentioning
confidence: 99%
“…Rural regional systems embody composite functional structures. Based on our previous research results [55], the functions of rural regional systems were simplified into production function (economic output), living function (population carrying), and ecological function (ecological service), while the cultural function was integrated into the nonagricultural industrial production function and cultural service ecological function, respectively. Accordingly, the measurement benchmarks were unified through functional value marketization, and the transformation modes were summarized through functional structure heterogeneity.…”
Section: Measurements Of Rural Transformationmentioning
confidence: 99%